A Metastudy of Journal of Employment Counseling: An Analysis of Publication Patterns From 2000 to 2019. Issue 4 (6th December 2020) - Siegler, Emily; Stafford, Carly; Zhou, Yi; Erford, Bradley T.; Crockett, Stephanie A.
Abstract : Articles published in the Journal of Employment Counseling from 2000 to 2019 were analyzed for trends over time related to author characteristics (i.e., domicile, gender, work setting, and leading contributors and institutions) and article content (i.e., typology, topical issues, research methodology, characteristics of participants, research design, statistics used, report of effect size and sample reliability and validity).